Continuous improvement of the institutional review board at one completely online university: a transferable framework. (1st October 2020) - Lehan, Tara J.
ABSTRACT: To protect human subjects to the fullest extent possible, stakeholders must make time to reflect as well as engage in continuous-improvement efforts regularly using a rigorous framework. At one completely online university that primarily grants graduate degrees, stakeholders informally expressed complaints relating to various policies and practices of the institutional review board (IRB). Therefore, complementary to a formal survey relating to IRB policies and practices, an environmental scan was conducted of (1) policies and practices at peer and 'top-ranked' institutions and (2) best practices cited in the relevant literature. Many of the resulting recommendations were adopted by the university's IRB to enhance its efficiency and effectiveness to support and serve student, faculty, and staff researchers more effectively. This framework can be implemented at other institutions at which researchers engage with the IRB from a distance.